2014
DOI: 10.1186/1471-2474-15-161
|View full text |Cite
|
Sign up to set email alerts
|

Subjective health complaints in patients with lumbar radicular pain and disc herniation are associated with a sex - OPRM1 A118G polymorphism interaction: a prospective 1-year observational study

Abstract: BackgroundEarlier observations show that development of persistent pain may be associated with the genetic variability in the gene encoding for the μ-opioid receptor 1, the OPRM1 A118G (rs1799971). The aim of this study was to investigate the association between OPRM1 genotype and subjective health complaints in patients with radicular pain and disc herniation.MethodsA prospective, 1-year observational study was conducted at a hospital back clinic, including 118 Caucasian patients with lumbar radicular pain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Two studies reported a positive association between the OPRM1 SNP rs179971 and poor recovery of pain in women with LRP [20, 21]. These data support the previous observation that some individuals, in particular in females, carrying the ORPM1 G allele have increased pain sensitivity [47, 48].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Two studies reported a positive association between the OPRM1 SNP rs179971 and poor recovery of pain in women with LRP [20, 21]. These data support the previous observation that some individuals, in particular in females, carrying the ORPM1 G allele have increased pain sensitivity [47, 48].…”
Section: Discussionsupporting
confidence: 84%
“…Olsen et al [20] and Hasvik et al [21] demonstrated that a genetic variant, OPRMI rs1799971 SNP, in the gene encoding OPRM1 receptor is associated with both pain and subjective health in LRP patients. The OPRM1 rs1799971 G allele increased the pain score in women, but reduced the pain score in men.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many studies have examined genetic influences on naltrexone responsitivity, particularly variation in the mu opioid receptor gene (OPRM1; Anton et al, 2008; Chamorro et al, 2012; Ray et al, 2010). Despite numerous studies of this relationship, as well as several reports that hormonal response naloxone is affected by OPRM1 (Chong et al, 2005; Hernandez-Avila et al, 2003; 2007) or that sex may mediate OPRM1 effects on pain responsivity and drug reinforcement (Fillingim et al, 2005; Hasvik et al, 2014; Ray et al, 2006), only a few laboratory studies have explored sex by OPRM1 effects on response to naltrexone, with mixed results (Ray et al, 2006; Setiawan et al, 2011). As such, future studies examining the relationship between OPRM1 or other genetic variants and naltrexone response should consider sex as a variable in their design.…”
Section: 0 Discussionmentioning
confidence: 99%
“…This modulation is probably found in the context of chronic pain and functional diseases. Therefore, the perception itself, tolerance and the emotional response to pain, are also associated to this "central modulation" along with gene expression and a particular environment (e.g., proteins acting at any point of the pain process like the periphery, the spinal cord or central nervous system) [34,35]. Accordingly, subjective perception of pain may sometimes arise from a normally painless stimulus.…”
Section: Painmentioning
confidence: 99%